Automotive simplex and duplex drum brake squeal analysis using the finite element method. (January 2022) - Dias, Anderson L; Rodrigues, Rômulo dN; Bezerra, Roberto dA; Lamary, Pierre
Despite the fact that disk brakes are used on almost entire mass produced vehicle, drum brakes are still applied on light-, medium-, and heavy-duty vehicles. However, both exhibit a high level of brake noises in which squeal is the most uncomfortable and one of the reasons behind high warranty costs that concern the automotive industry. Hence, the development of prediction methods and models of brake noise have prompted significant efforts. This study intends to analyze two types of drum brakes of a commercial automotive application. Their parametric finite element model comprises drum, shoes, and frictional linings and are submitted to a computational process that includes static calculations of the system under the brake forces to get a pre-stress state around which is computed the complex eigenvalues of the system which characterize their stability. These calculations indicate the unstable frequencies of the entire system. After the design of experiments (DOE) process, the influence of drum brake parameters on system stability can be seen. The friction coefficient and Young's modulus presented a strong correlation with squeal incidence. At the end is presented a comparison and the optimal material parameters to decrease squeal noise occurrence of these brakes.